Colonialist narrative in a post-colonial era travel writing, Into the Heart of Borneo - Gheeta Chandran; Ravichandran Vengadasamy (Penerbit Universiti Kebangsaan Malaysia, 2018)
Travel writings have long served as important points of reference for Western academicians, travellers and those generally associated with the business of conquest and trade. More often than not, these sources of references had depicted the lands and people of the ‘new world,’ usually the East or Africa, as being wild, savage and in dire need of European intervention for the creation of civilized societies. Therefore, it would be of great interest to both scholars and travellers to find out if the colonialist representations still persist in a post-colonial era Western travel writing about the East. The current study examines the ways in which Redmond O’Hanlon, an English naturalist, constructs and represents the natives and the land of Sarawak in his travel writing, Into the Heart of Borneo (1984). The study aims to find out if O'Hanlon’s representation of Sarawak and its natives have progressed from the depictions found in the travel writings of his colonialist predecessors. The discussion of findings is preceded by a brief explanation of Edward Said’s notion of Orientalism, which provides the theoretical basis for the analysis of the travel novel. The paper highlights that there has been no real evolution in the travel narrative used by O’Hanlon to describe Sarawak and its natives from the colonial heyday of travel literature.